2016
DOI: 10.5021/ad.2016.28.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate-Mediated Alteration of the MicroRNA Expression Profile in 5α-Dihydrotestosterone-Treated Human Dermal Papilla Cells

Abstract: BackgroundDihydrotestosterone (DHT) induces androgenic alopecia by shortening the hair follicle growth phase, resulting in hair loss. We previously demonstrated how changes in the microRNA (miRNA) expression profile influenced DHT-mediated cell death, cell cycle arrest, cell viability, the generation of reactive oxygen species (ROS), and senescence. Protective effects against DHT have not, however, been elucidated at the genome level.ObjectiveWe showed that epigallocatechin gallate (EGCG), a major component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Similar results for miR-140-3p were obtained under EGCG treatment in chondrocyte [102]. Furthermore, EGCG induced the increase of miR-3663-3p, miR-1181, miR-3613-3p, miR1281, and miR-1539 and the decrease of miR-221-5p, miR-374b, miR-4306, miR-500a-5p, and miR590-5p in human dermal papilla cells [108] from scalp hair. The sensitivity of the scalp is also higher in migraine, and this latter miR was found downregulated in humans suffering from pain-migraine.…”
Section: Egcg and Micrornassupporting
confidence: 81%
“…Similar results for miR-140-3p were obtained under EGCG treatment in chondrocyte [102]. Furthermore, EGCG induced the increase of miR-3663-3p, miR-1181, miR-3613-3p, miR1281, and miR-1539 and the decrease of miR-221-5p, miR-374b, miR-4306, miR-500a-5p, and miR590-5p in human dermal papilla cells [108] from scalp hair. The sensitivity of the scalp is also higher in migraine, and this latter miR was found downregulated in humans suffering from pain-migraine.…”
Section: Egcg and Micrornassupporting
confidence: 81%
“…However, Shin et al accidentally discovered a hormetic effect of EGCG with human DPCs in 2016. 27 Unaware of the earlier 2008 report of Li et al, 26 they cited the earlier 2003 report of Chung et al 28 confirming the “concentration-dependent dual function” of EGCG, showing a stimulation of human epidermal keratinocyte proliferation (Figure S3). At the optimal concentration of 10 μM, Shin et al reported that EGCG inhibited DHT-induced cellular senescence and reactive oxygen species (ROS) levels.…”
Section: Resultsmentioning
confidence: 75%
“…At the optimal concentration of 10 mM, Shin et al reported that EGCG inhibited DHTinduced cellular senescence and reactive oxygen species (ROS) levels. 27 Furthermore, the 10-mM EGCG concentration altered DHT effects on MiRNA (ie, 13 upregulated and 40 downregulated effects; Figure S4).…”
Section: Hair Growthmentioning
confidence: 99%
“…Dihydrotestosterone (DHT) is known to induce androgenic alopecia by shortening the hair follicle growth phase, resulting in hair loss. DHT damages DPCs by upregulation of Dickkopf 1 (DKK‐1), induction of cell death, increase in ROS and senescence in DPCs .A variety of compounds have demonstrated protective effect against DHT induced stress in DPCs .…”
Section: Protective Effect In Hair Growth Against Stressmentioning
confidence: 99%